Reevaluating Educational Philosophy in the Age of Technological Transformation: A Systematic Review of Progressive Pedagogies and Digital Integration - Khoirul Huda; S Sariyatun (Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study presents a systematic literature review examining the intersection of progressive education and digital technology integration in contemporary learning environments. The objective is to analyze how digital tools support or challenge progressive pedagogical practices across global educational contexts. This review is categorized into five core themes for a summary of integrating progressive pedagogies, reflective learning, experiential practice, digital equity, and epistemological shifts. The methodology involved synthesizing findings from 15 selected academic sources, mapped across five thematic sections, including pedagogical integration, reflective digital practices, philosophical adaptation, traditionalism versus progressivism, and epistemological debates. Findings indicate that digital platforms enhance critical thinking, agency, and inclusivity when aligned with progressive ideals. Yet, challenges such as resistance to change, lack of digital infrastructure, and persistent traditionalist frameworks hinder broad adoption. The review underscores the growing epistemological transformation in education, where knowledge is increasingly seen as dynamic and co-constructed through digital interaction. These findings offer valuable implications for educators and policymakers seeking to implement equitable, student-centered approaches in the digital age. The study contributes to ongoing discourse on educational innovation by highlighting critical tensions and future possibilities for progressive pedagogy.